A mix-method study on students’ demotivating factors in learning English in higher education context - Syamsul Bahri; Siti Khasinah; Nabila Fajarina (Jurnal Pengembangan Profesi Guru dan Dosen, 2025)
This study attempts to explore students’ demotivating factors in learning English at Department of English Language Education. This research employed a mixed-method research which used questionnaire and interview technique. The participants consisted of 63 students from Department of English Language Education. The finding showed that the students reflected on teaching material, teaching process and teaching content factors, teaching facilities and teaching environment, the relationship between lecturers and students, lecturers’ teaching competence and attitude of lecturers, experience of failure and lack of confidence, unclear study goal factor, significance others, the scheduling system and the usage of native language in language learning process as their demotivating factors in learning English. Teaching material, process and content found out to be the major factor that decreases students’ interest in learning English. This research is expected to enrich the literature research of demotivation in learning English and to provide an adequate information to the educators to help the students eliminate the demotivating factors